Effects of solid-state fermentation with two filamentous fungi on the total phenolic contents, flavonoids, antioxidant activities and lipid fractions of plum fruit (Prunus domestica L.) by-products. (15th October 2016) - Dulf, Francisc Vasile; Vodnar, Dan Cristian; Socaciu, Carmen
Highlights: Solid-state fermentation (SSF) of plum by-products with A. niger and R. oligosporus. Phenolic compounds and antioxidant levels increased significantly by SSF. Plum kernel oil yield increased by 21.90% for SSF with A. niger. Polar lipids were enriched with n-3 polyunsaturated fatty acids. Abstract: Evolutions of phenolic contents and antioxidant activities during solid-state fermentation (SSF) of plum pomaces (from the juice industry) and brandy distillery wastes with Aspergillus niger and Rhizopus oligosporus were investigated. The effect of fermentation time on the oil content and major lipid classes in the plum kernels was also studied. Results showed that total phenolic (TP) amounts increased by over 30% for SSF with Rhizopus oligosporus and by >21% for SSF with A. niger . The total flavonoid contents presented similar tendencies to those of the TPs. The free radical scavenging activities of methanolic extracts were also significantly enhanced. The HPLC-MS analysis showed that quercetin-3-glucoside was the major phenolic compound in both fermented plum by-products. The results also demonstrated that SSF not only helped to achieve higher lipid recovery from plum kernels, but also resulted in oils with better quality attributes (high sterol ester and n-3 PUFA-rich polar lipid contents).